Susceptibility ofKlebsiella pneumoniaeon coriander leaves to liquid- and vapor-phase ethanol - Warawut Krusong; Soisuda Pornpukdeewatana; Montinee Teerarak (My University, 2016)
The bio-control of ethanol on Klebsiella pneumoniae on fresh coriander leaves for significantly reducing consumer health risk was investigated. Washed and sterilized leaves of coriander were inoculated with K. pneumoniae cultured in Trypticase Soy broth. Susceptibility of the K. pneumoniae to liquid- and evaporated vapor-phase ethanol (EVE) was then examined in vitro. Complete inhibition of K. pneumoniae was found with 18% (v/v) liquid ethanol. Exposure for 15 min to EVE (9.00 ± 0.8 mmol L−1) completely destroyed K. pneumoniae (4.04 ± 0.02 log CFU/ml) spread on Mueller Hilton agar at 30 ± 2°C. The effect of EVE with and without evaporated water vapor (EWV) on the susceptibility of K. pneumoniae on fresh coriander leaves was examined. While exposure to EVE affected the survival of K. pneumoniae, the degree of reduction depended on both the inoculation level and the EWV. Complete reduction of K. pneumoniae was achieved for the low inoculation level by EVE alone (37 ± 2% relative humidity; RH) but susceptibility was reduced with EWV (high RH; 80 ± 2%). Scanning electron microscope (SEM) images of inoculated coriander leaves confirm the effects of EVE in reducing levels of K. pneumoniae. Exposure to EVE alone proved an effective bio-control for K. pneumoniae on fresh coriander leaves.
Keywords: Essential Oils and Antimicrobial Activity